On the misuse of regressions of price on the HHI in merger review. (28th May 2022) - Miller, Nathan; Berry, Steven; Scott Morton, Fiona; Baker, Jonathan; Bresnahan, Timothy; Gaynor, Martin; Gilbert, Richard; Hay, George; Jin, Ginger; Kobayashi, Bruce; Lafontaine, Francine; Levinsohn, James; et al.
Abstract: The article explains why regressions of price on HHI should not be used in merger review. Both price and HHI are equilibrium outcomes determined by demand, supply, and the factors that drive them. Thus, a regression of price on the HHI does not recover a causal effect that could inform the likely competitive effects of a merger. Nonetheless, economic theory is consistent with the legal presumption that a merger is likely to have adverse competitive effects if it occurs in a concentrated market and makes that market more concentrated.